2015
DOI: 10.1007/s00520-015-3005-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a physical therapy program combined with manual lymphatic drainage on shoulder function, quality of life, lymphedema incidence, and pain in breast cancer patients with axillary web syndrome following axillary dissection

Abstract: PT improves shoulder function, pain, and QOL in breast cancer patients with AWS and combined with MLD decreases arm lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(143 citation statements)
references
References 36 publications
7
125
1
10
Order By: Relevance
“…In the other variables, with no statistically significant effect after adjustment, the Experimental Group maintained the favorable estimate effect. This matches other studies that report a statistically significant GHS improvement in the same postsurgery period in the group submitted to physiotherapy or to an exercise program when compared to a Control Group [19,29,31,47]. In the other function and symptoms scales there were no statistically significant differences between groups.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the other variables, with no statistically significant effect after adjustment, the Experimental Group maintained the favorable estimate effect. This matches other studies that report a statistically significant GHS improvement in the same postsurgery period in the group submitted to physiotherapy or to an exercise program when compared to a Control Group [19,29,31,47]. In the other function and symptoms scales there were no statistically significant differences between groups.…”
Section: Discussionsupporting
confidence: 89%
“…This matches the results of other studies in which, during the same period, there were no statistically significant differences between groups in the scales for Arm Symptoms [48], Breast Symptoms [48,49], Physical Functioning, Role Functioning, and Social Functioning [28,48]. However, in some studies over the same period, there was a statistically significant improvement in the Experimental versus Control Group in Physical Functioning [19,22,31], Role Functioning [19,22,25], Emotional Functioning [19,22], Social Functioning [19,22], Pain [19,25,29], Breast Symptoms [19], Arm Symptoms [19,31], and Fatigue [25].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Though volumetric measurements serve as the most commonly used clinical mechanism for quantifying treatment impact, there is question whether this indirect volumetric measurement is sensitive enough to discern the impact of the CDT components. Multiple studies have been designed in attempts to investigate volumetric changes as a response to MLD over time and some find MLD successful at reducing limb volume 28,29 while others have found no effect. 30,31 BIS has been used to investigate its potential to identify early signs of lymphedema before overt edema is detected and before the early symptoms of arm heaviness and generalized ache.…”
Section: Quantitative Changes After Mldmentioning
confidence: 99%
“…Many previous studies showed that physical therapy has efectiveness in breast cancer patients [25,26]. In general, combined physical therapy is efective to treat postoperative lymphedema, Clinical Physical Therapypain, and impaired ROM after treatment for breast cancer [26].…”
Section: Physical Therapymentioning
confidence: 99%